The safety and effects of the beta-blocker, nadolol, in mild asthma: An open-label pilot study (2008)
ABSTRACT: Beta-blockers are currently contraindicated in asthma because their acute administration may be associated with worsening bronchospasm. However, their effects and safety with their chronic administration are not well evaluated. The rationale for this pilot study was based on the paradigm shift that was observed with the use of beta-blockers in congestive heart failure which once contraindicated because of their acute detrimental effects, have now been shown to reduce mortality with their chronic use. We hypothesized that certain beta-blockers may also be safe and useful in chronic asthma therapy. In this prospective, open-label, pilot study, we evaluated the safety and effects of escalating doses of the beta-blocker, nadolol, administered over 9 weeks to 10 subjects with mild asthma. Dose escalation was performed on a weekly basis based on pre-determined safety lung function, asthma control and hemodynamic parameters. The primary objective was to evaluate safety and secondary objectives were to evaluate effects on airway hyperresponsiveness, and indices of respiratory function. The escalating administration of nadolol was well tolerated. In 8 out of the 10 subjects, nine weeks of nadolol treatment produced a significant, dose-dependent increase in PC20 that reached 2.1 doubling doses at 40 mg (p < 0.0042). However, there was also a dose-independent 5% reduction in mean FEV1 over the study period (p < 0.01). We conclude that in most patients with mild asthma, the dose-escalating administration of the beta-blocker, nadolol, is well tolerated and may have beneficial effects on airway hyperresponsiveness. Our findings warrant further testing in future larger trials.